Multiband diffusion‐weighted MRI of the eye and orbit free of geometric distortions using a RARE‐EPI hybrid. (9th January 2018) - Paul, Katharina; Huelnhagen, Till; Oberacker, Eva; Wenz, Daniel; Kuehne, André; Waiczies, Helmar; Schmitter, Sebastian; Stachs, Oliver; Niendorf, Thoralf
Abstract : Diffusion‐weighted imaging (DWI) provides information on tissue microstructure. Single‐shot echo planar imaging (EPI) is the most common technique for DWI applications in the brain, but is prone to geometric distortions and signal voids. Rapid acquisition with relaxation enhancement [RARE, also known as fast spin echo (FSE)] imaging presents a valuable alternative to DWI with high anatomical accuracy. This work proposes a multi‐shot diffusion‐weighted RARE‐EPI hybrid pulse sequence, combining the anatomical integrity of RARE with the imaging speed and radiofrequency (RF) power deposition advantage of EPI. The anatomical integrity of RARE‐EPI was demonstrated and quantified by center of gravity analysis for both morphological images and diffusion‐weighted acquisitions in phantom and in vivo experiments at 3.0 T and 7.0 T. The results indicate that half of the RARE echoes in the echo train can be replaced by EPI echoes whilst maintaining anatomical accuracy. The reduced RF power deposition of RARE‐EPI enabled multiband RF pulses facilitating simultaneous multi‐slice imaging. This study shows that diffusion‐weighted RARE‐EPI has the capability to acquire high fidelity, distortion‐free images of the eye and the orbit. It is shown that RARE‐EPI maintains the immunity to B 0 inhomogeneities reported for RARE imaging. This benefit can be exploited for the assessment of ocular masses and pathological changes of the eye and the orbit. Abstract : This study shows that diffusion‐weighted rapid acquisition with relaxation enhancement‐echo planar imaging (RARE‐EPI) has the capability to acquire distortion‐free images of the eye and orbit with ample diffusion contrast. The results underpin the challenges of ocular imaging at 3.0 T and 7.0 T for EPI and demonstrate that these issues can be offset using accelerated RARE‐based approaches. This benefit can be exploited for the assessment of spatial arrangements of the eye segments and their masses with the goal to provide guidance in the diagnostic assessment and treatment of ophthalmological diseases.